2006
DOI: 10.1007/s10461-006-9173-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a Community Sample about Participation in Future HIV Vaccine Trials in South India

Abstract: Focus group discussions were conducted to assess factors that might impact participation of subgroups in Chennai for future HIV vaccine trials. The participants were 112 men and women representing the following: (1) transport workers; (2) clients who attended a sexually transmitted disease clinic; (3) injection drug users; (4) men having sex with men; (5) women in sex work; and (6) monogamous married women. Participants expressed an intense interest in future HIV vaccine trials. Willingness to participate in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
(15 reference statements)
1
30
0
Order By: Relevance
“…Focus group research has reported that commercial sex workers, for example, would have few fears of HIV once they have been vaccinated, diminishing their motivation to have customers use condoms [8]. Individuals perceive HIV as less of a threat in the event that they were vaccinated and that they would likely increase their sexual risk behaviors following vaccination.…”
Section: Hiv Vaccinesmentioning
confidence: 99%
“…Focus group research has reported that commercial sex workers, for example, would have few fears of HIV once they have been vaccinated, diminishing their motivation to have customers use condoms [8]. Individuals perceive HIV as less of a threat in the event that they were vaccinated and that they would likely increase their sexual risk behaviors following vaccination.…”
Section: Hiv Vaccinesmentioning
confidence: 99%
“…During phase I (qualitative), 12 focus group discussions (FGDs) were conducted, the findings of which are presented elsewhere. 4 During the Phase II (quantitative) study, 501 study participants were enrolled. These included five highrisk groups composed of the following: transport workers (TWs), persons diagnosed with a recent sexually transmitted infection (STI) from government hospitals and NGOs (STIs), injection drug users (IDUs), men having sex with men (MSMs), and female sex workers (FSWs).…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…The few WTP studies conducted in India [13][14][15][16] provide limited information due to small samples of MSM subsumed in larger studies of vulnerable groups and lack of exploration of what may be population-specific phenomena among MSM in the Indian context. Diversity within MSM communities in India, including by socioeconomic status and sexual self-identification [17], further suggest the need to explore potential subpopulation differences in WTP and trial-related concerns.…”
Section: Introductionmentioning
confidence: 99%